Moderating Auditor Ethics: Examining Independence, Competence, Task Complexity, Time Pressure, and Professional Skepticism Influence on Audit Quality - Helen Sondang Glroia; Hermi Hermi (Publikasi Indonesia, 2023)
This study aims to examine and analyze the Effect of Independence, Competence, Task Complexity, Time Pressure, and Professional Skepticism of Auditors on Audit Quality with Auditor Ethics as Moderating Variable. This research was conducted using quantitative methods. The population in this study are several auditors who have participated in filling out questionnaires from several KAP’s in 2021. Where the authors determine the population using random sampling. And Multiple Linear Regression analysis technique. Based on the results of this study indicate that Independence, Competence, Task Complexity and Professional Skepticism have a positive effect on Audit Quality. Meanwhile, Time Pressure has no effect on Audit Quality. Auditor Ethics can strengthen the influence of Auditor Independence, Competence, Task Complexity, and Professional Skepticism on Audi Quality. Meanwhile, Auditor Ethics weakens the influence of Time Pressure on Audit Quality.